LARVICIDAL ACTIVITY OF CLERODENDRON INERME GAERTN. EXTRACTS AGAINST AEDES AEGYPTI L. AND CULEX QUINQUEFASCIATUS SAY. MOSQUITO SPECIES - Patil, Prabhakargouda B; V Kallapur, Shrinivas; Kallapur, Vasant L; Holihosur, Shankar N (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: In the present investigation, larvicidal activity of organic solvents extracts of C. inerme plant were tested against third and fourth instar larvae of Ae. aegypti and Cx. quinquefasciatus. Methods: Extracts of C. inerme sundried leaf powder were prepared by soxhlation using chloroform, petroleum ether and hexane and were tested for larvicidal activity against third and fourth instar larvae of Ae. aegypti and Cx. quinquefaciatus. Results: The extract exhibiting the highest larvicidal activity against Ae. aegypti was found to be hexane extract with LC50 values of 87.2 (24 hour) and 81.5 ppm (48 hours) against third instar larvae and 121.1ppm (24 hours) and 100.3 ppm (48 hours) against fourth instar larvae. The hexane extract tested against third and fourth instar larvae of Cx. quinquefasciatus showed LC50 values of 127.1 ppm (48 hours) against third instar larvae and 240.7 ppm (24 hours) and 141.1 ppm (48 hours) concentrations against fourth instar larvae. Observations on the dead larvae in the treated groups revealed interference in the developmental period affecting the mid gut region and extrusion of peritropic membrane at the posterior end. Conclusion: Our results suggest that the hexane extract of the C. inerme plant leaves possess promising larvicidal properties against Ae. aegypti, a fresh water breeding species, and against Cx. quinquefasciatus larvae, a species found breeding in polluted water. In conclusion the hexane extract can be a potential botanical insecticide for treating mosquito breeding sources of wide nature.